A prevalence of elevated ARR in rural Selangor - Saud Gany, Siti Liyana; Shahar, Mohammad Arif; Sukor, Norlela; Omar , Ahmad Marzuki; Ab Wahab, Norasyikin; MY, Yusniza; Md Zain, Rabizah; Long , Kha Ching; Mohd Razali, Amyliation; Zainuddin, Noradilah; Mat, Nurul Hani; Mender, Fadlin; et al. (ASEAN Federation of Endocrine Societies, 2015)
Abstract The objective of this study was to determine the prevalence of elevated Aldosterone Renin Ratio (ARR) in Rural Selangor.